Assessing the Impact of Wastewater Discharge on Seawater Quality in the Asban Area of Zawiya City: A Comparative Analytical Study of Chemical and Biological Indicators (Al-Farooq Journal of Sciences, 2026)
This study primarily aims to assess the impact of wastewater discharge on seawater quality in the Asban area of ​​Zawiya city. This is achieved through the analysis and comparison of several chemical and biological indicators across the study samples. Specifically, the study measured various seawater quality indicators in the Asban area, including pH, total dissolved solids (TDS), total hardness, calcium, magnesium, nitrates, and biochemical oxygen demand (BOD). The study also aimed to determine the degree of change in seawater properties within the study area based on laboratory analysis results from samples taken from different locations. Furthermore, the study compared the values ​​of chemical and biological indicators between samples located near and far from the wastewater discharge point. The study concluded that seawater quality in the Asban area of ​​Zawiya city varies among the samples, indicating spatial variations in water characteristics. The results from 2024 showed that pH values ​​ranged between 7.00 and 7.75, values ​​close to neutral, making this indicator less indicative of pollution compared to some other indicators. Total dissolved solids (TDS) values ​​were also analyzed. The samples showed a convergence, ranging between 48.007 and 50.007, indicating limited variation in this indicator during 2024. The total hardness index (T.H.) showed a clear variation between the samples, particularly between samples D and A, reflecting a change in some of the chemical properties of the seawater
Keywords: Wastewater - Seawater – Angle Analytical Study - Chemical and Biological Indicators